Utilization of Blockchain Technology Revolution in Electronic ID Card Data Integrity - Kurniawan, Irvan Arif; Yusman, Dede; Aprilia, Indri Okshana (APTISI Transactions on Management (ATM), 2021)
KTP is a proof of identification issued by the implementing agency that applies throughout the territory of the Unitary State of the Republic of Indonesia. The existence of KTP is recognized as very important in daily life because it is used in all activities or any series of administrative transactions. Field studies found the number of cases of Asphalt ID cards (original but fake) used as a means of media fraud. Because ID cards are very easy to falsify this makes it difficult to identify cases of data misappropriation. The focus of the research was the utilization of Blockchain, by applying distributed consensus and cryptography in improving the administration management system of KTP to identify the existence of fake IDs and double data. The research method used is descriptive analysis method and literature study. By implementing the decentralization and cryptographic system owned by Blockchain, it is expected to minimize the occurrence of identity misappropriation, as well as be able to be a technology capable of contributing to the success of aspects of state administration governance systems.